Dilematika Pencatatan Perkawinan dalam Permendagri No. 109 Tahun 2019: Harmonisasi dengan UU No. 1/1974 - Azmil Fauzi Fariska (Jurnal Indragiri Penelitian Multidisiplin, 2026)
This study aims to examine the dilemmas of marriage registration by focusing on a normative analysis of the relationship between Article 2 of Law No. 1 of 1974 on Marriage and the regulation of the Statement of Absolute Responsibility (SPTJM) under Regulation of the Minister of Home Affairs No. 109 of 2019. It further seeks to assess whether the administrative recognition of “unregistered marriages” is consistent with the objectives of marriage registration from the perspectives of national law and maqāṣid al-sharī‘ah. The methodology employed is normative legal research (doctrinal legal research), utilizing both a statutory approach and a conceptual approach. This study concludes that the administrative recognition of “unregistered marriages” through the Statement of Absolute Responsibility (SPTJM) under Regulation of the Minister of Home Affairs No. 109 of 2019 functions as a pragmatic administrative mechanism to ensure access to population administration services. However, it is not fully consistent with the objectives of marriage registration as mandated by Article 2 of Law No. 1 of 1974 on Marriage. From the perspective of national law, such administrative recognition risks undermining legal certainty and the comprehensive protection of civil rights if it is treated as a substitute for formal marriage registration. From the perspective of maqāṣid al-sharī‘ah, formal marriage registration is more aligned with the realization of public welfare (maṣlaḥah), particularly in safeguarding lineage (ḥifẓ al-nasl) and family rights. Therefore, administrative recognition of unregistered marriages should be positioned strictly as a temporary measure and systematically directed toward the fulfillment of formal legal registration through lawful judicial or administrative procedures.